Method Optimization: Analysis of Benzbromarone and Tolfenamic Acid in Citrus Tissues and Soil Using Liquid Chromatography Coupled With Triple-Quadrupole Mass Spectrometry - Zhang, Dan; da Silva, Danilo R.; Garrett, Timothy J.; Gonzalez, Claudio F.; Lorca, Graciela L. (Frontiers in Plant Science, 2020)
Herein, an analytical method was developed for extraction and quantification of benzbromarone and tolfenamic acid in citrus and soil matrices using liquid-liquid extraction followed by liquid chromatography-triple quadrupole-tandem mass spectrometry analysis. The compounds were extracted using 0.1% formic acid in 6:4 ethyl acetate and n-hexane solution, and the analytes were separated using a mixture of 0.1% formic acid in ultrapure water and 0.1% formic acid in acetonitrile as mobile phase. A six-point in-matrix calibration curve was constructed providing good linearity with coefficients of determination R2≥0.98. The limits of detection and quantification for benzbromarone and tolfenamic acid were 3.0 and 10.0 µg/kg in roots, peel, juice, and soil, and 4.0 and 12.0 µg/kg for leaves samples, respectively. The method yielded excellent recoveries between 81.3-101.2%, with relative standard deviation ≤9.5% in the matrices. The developed technique provides a simple and sensitive method for the determination of the chemicals and can be applied to agricultural practices.